High IGFBP2 Expression Correlates with Tumor Severity in Pediatric Rhabdomyosarcoma - Tombolan, Lucia (American Society for Investigative Pathology, 2011)
Rhabdomyosarcoma (RMS) is the most common childhood sarcoma and is identified as either the embryonal or alveolar (ARMS) subtype. In approximately 75% of cases, ARMSs are characterized by specific chromosomal translocations that involve PAX and FKHR genes. ARMS gene expression signatures vary, depending on the presence or absence of the translocations. Insulin-like growth factor–binding protein 2 (IGFBP2) is strongly overexpressed in translocation-negative RMS. Because IGFBP2 is associated with tumorigenesis, we investigated its functional role in RMS. An analysis of IGFBP2 distribution in RMS cell lines revealed a strong accumulation in the Golgi complex, in which morphological characteristics appeared peculiarly modified. After silencing IGFBP2 expression, our microarray analysis revealed mostly cell cycle and actin cytoskeleton gene modulations. In parallel, IGFBP2-silenced cells showed reduced cell cycle and rates of invasion and decreased seeding in the lungs after tail vein injections in immunodeficient mice. An analysis of IGFBP2 mRNA and protein localization in human tumors showed abnormal protein accumulation in the Golgi complex, mostly in PAX/FKHR-negative RMS. Moreover, an analysis of patients with RMS revealed the presence of conspicuous circulating levels of IGFBP2 proteins in children with highly aggressive RMS tumors. Taken together, our data provide evidence that IGFBP2 contributes to tumor progression and that it could be used as a marker to better classify clinical and biological risks in RMS.